Mechanical Properties of Magnetron Sputtered Free Standing Mg-Ag Alloy Films - Jessen, Lea K.; Zamponi, Christiane; Quandt, Eckhard (Frontiers in Materials, 2019)
Magnesium based alloys gained great interest for medical biodegradable applications. Limitations arise from high corrosion rates and mechanical properties of the Mg based alloys. In recent work it was shown that the corrosion rate of a precipitate free Mg-6Ag thin film can be reduced by a factor of three compared to pure sputtered Mg. As Mg-6Ag combines the very promising corrosion results with a potential therapeutically use of Ag ions, the investigation of their mechanical properties is needed for a full characterization of Mg-Ag alloys as biodegradable material. In this work the Ag content was varied from 2 wt% to 10 wt%. The investigated thin film samples were dog-bone shaped samples with a thickness of 20 µm. The samples were fabricated by a combination of UV lithography, sacrificial layer technique and magnetron sputtering. The mechanical properties were determined using uniaxial tensile test. Compared to pure Mg samples fabricated by the same processing route the yield strength is approximately doubled for Ag containing samples. For films with a Ag concentration up to 8 wt% the elongation at fracture reaches a value of 7%. Further increase of the Ag concentration leads to lower elongation at fracture. Thus, especially due to the low corrosion rate, Mg-6Ag shows the optimum of all investigated alloys, with a yield strength of 310 MPa and an elongation at fracture of 6%.